Frontline Care: The Role of Hospital Pharmacists During the COVID-19 Pandemic in North Macedonia - Zorica Naumovska; Biljana Lazarova; Maja Kovaceva; Aleksandra Kapedanovska Nestorovska; Maja Simonoska Crcarevska; Evgenija Mihajlova; Aleksandar Dimkovski (Pharmaceutical Science: New Insights and Developments Vol. 6, 2025)
Background: Hospital pharmacists played a pivotal role during the COVID-19 pandemic. As part of the team alongside nurses, physicians, and respiratory therapists, hospital pharmacists contribute to COVID-19 management protocols, warranting sufficient medication supply by managing critical drug, medical devices, or personal protection equipment (PPE) shortages through the implementation of conservation strategies and sourcing alternatives. Aims: The aim of this chapter is to evaluate the knowledge, attitudes, level of engagement, and the impact of the COVID-19 pandemic on the daily professional practice of hospital pharmacists in the Republic of North Macedonia, highlighting their critical role as frontline healthcare providers during the crisis. Methodology: A questionnaire-based study was conducted among hospital pharmacists and pharmacy technicians. The study was conducted in the Republic of North Macedonia in July 2022. It involved hospital pharmacists of varying ages and levels of professional experience from five different cities. Among the respondents, 95.8% were female. Focus-methodology group approach was used when designing and structuring the questionnaire was carried out. Results: The results highlighted the pharmacists’ knowledge of COVID-19 strains, disinfectants, and current therapeutic options. The study revealed that 37.5% of participants always, 20.8% frequently, and 29.2% occasionally felt depressed or fatigued during the pandemic, though 83% never considered leaving their jobs. The survey found that 87.5% of pharmacists experienced shortages of masks, gloves, and disinfectants early in the pandemic, and 100% noted the increased cost of these supplies. Only 22.7% were not consulted for therapy advice for hospitalised COVID-19 patients. Opinions varied on the use of off-label drugs, and pharmacists played a key role in pharmacovigilance practices, with 36.4% reporting adverse events. The study confirmed the vital role of hospitals in promoting rational antibiotic use and antimicrobial resistance programs. Conclusion: This study, the first of its kind conducted in the post-pandemic period in the Republic of North Macedonia, highlights the essential and multifaceted role of hospital pharmacists during the COVID-19 crisis. It underscores the need for formal inclusion of clinical pharmacists in healthcare processes through clear legal frameworks and written procedures. Furthermore, it emphasises the importance of pharmacist engagement in clinical practice and research, particularly in monitoring drug prescription, preparation, and administration, to ensure safe and effective patient care.